Association Between Surgeon Sex and Days Alive at Home Following Surgery: A Population-Based Cohort Study - Kiyan Heybati, BHSc; Raj Satkunasivam, MD, MS; Khatereh Aminoltejari, MD, MSc, FRCSC; Hannah S. Thomas, MBChB, MS; Arghavan Salles, MD, PhD; Natalie Coburn, MD, MPH; Frances C. Wright, MD, Med, FRCSC; Lesley Gotlib Conn, PhD; Amy N. Luckenbaugh, MD; Sanjana Ranganathan, MD; Carlos Riveros, MD; Colin McCartney, MBChB, PhD, FRCA, FFARCSI, FRCPC; et al. (Annals of Surgery Open)
Objective:. The objective of this study was to measure potential associations between surgeon sex and number of days alive and at home (DAH). Background:. Patients treated by female surgeons appear to have lower rates of mortality, complications, readmissions, and healthcare costs when compared with male surgeons. DAH is a validated measure, shown to better capture the patient experience of postoperative recovery. Methods:. We conducted a retrospective study of adults (≥18 years of age) undergoing common surgeries between January 01, 2007 and December 31, 2019 in Ontario, Canada. The outcome measures were the number of DAH within 30-, 90-, and 365-days. The data was summarized using descriptive statistics and adjusted using multivariable generalized estimating equations. Results:. During the study period, 1,165,711 individuals were included, of which 61.9% (N = 721,575) were female. Those managed by a female surgeon experienced a higher mean number of DAH when compared with male surgeons at 365 days (351.7 vs. 342.1 days; P < 0.001) and at each earlier time point. This remained consistent following adjustment for covariates, with patients of female surgeons experiencing a higher number of DAH at all time points, including at 365 days (343.2 [339.5–347.1] vs. 339.4 [335.9–343.0] days). Multivariable regression modeling revealed that patients of male surgeons had a significantly lower number of DAH versus female surgeons. Conclusions:. Patients of female surgeons experienced a higher number of DAH when compared with those treated by male surgeons at all time points. More time spent at home after surgery may in turn lower costs of care, resource utilization, and potentially improve quality of life. Further studies are needed to examine these findings across other care contexts.